2013
DOI: 10.1136/jnnp-2013-305296
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in Charcot-Marie-Tooth disease type 1

Abstract: In addition to known risk factors, CMT may predispose to OSA. RLS is highly prevalent not only in axonal subtypes of CMT but also in primarily demyelinating subforms of CMT. PLMS are common in CMT1, but do not significantly impair sleep quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 35 publications
1
38
1
8
Order By: Relevance
“…A significant portion of patients had mixed apnea. It was suggested that the particular tendency for OSA in those patients may be related to spread of the neuropathy to the pharyngeal muscles (90). …”
Section: Congenital Neuropathiesmentioning
confidence: 99%
“…A significant portion of patients had mixed apnea. It was suggested that the particular tendency for OSA in those patients may be related to spread of the neuropathy to the pharyngeal muscles (90). …”
Section: Congenital Neuropathiesmentioning
confidence: 99%
“…It is unknown to what extent chronic intermittent hypoxemia in OSAS causes damage to the motor and sensory peripheral nerve, but muscle action potential and sensory nerve action potential amplitudes are significantly reduced in the nerves outside UA in patients with OSAS suggesting that axonal damage exists in patients with OSAS to a greater extent than previously thought [24]. On the other hand, association between OSAS and sensory neuropathy, and nerve damage outside the UA [18,[25][26][27], type 2 or type 1A diabetic neuropathy, and axonal subtypes of Charcot-Marie-Tooth disease [28][29][30][31] has been also demonstrated. Of particular interest is the epidemiological association between OSAS and anterior ischemic optic neuropathy [32] although a concluding rapport cannot be established [33].…”
Section: The Neurological Theory Of Osas and The Upper Airways Remodementioning
confidence: 81%
“…Among the quantitative studies, two referred to themselves as descriptive (Gemignani et al, 1999; Padua et al, 2008a), while the remaining studies employed comparisons among groups (Rubinsztein et al, 1998; Dematteis et al, 2001; Pfeiffer et al, 2001; Teunissen et al, 2003; Vinci et al, 2005; Padua et al, 2006, 2008b, 2008c; Kalkman et al, 2007; Dziewas et al, 2008; Redmond et al, 2008; Hattan et al, 2009; Phillips et al, 2009; Vinci et al, 2009; Boenterd et al, 2010; Calvert et al, 2012; Boentert et al, 2014). …”
Section: Resultsmentioning
confidence: 99%
“…Considering the specific aims of the evaluated studies, it was possible to divide them into two groups, as follows: (a) studies investigating the comorbidity of psychiatric disorders in patients with CMT (Rubinsztein et al, 1998; Gemignani et al, 1999; Dematteis et al, 2001; Pfeiffer et al, 2001; Arnold et al, 2005; Padua et al, 2006, 2008a; Kalkman et al, 2007; Dziewas et al, 2008; Hattan et al, 2009; Phillips et al, 2009; Vinci et al, 2009; Boenterd et al, 2010) and (b) studies evaluating the impact of the CMT symptoms on the quality of life (Teunissen et al, 2003; Arnold et al, 2005; Vinci et al, 2005; Padua et al, 2006, 2008a, 2008b, 2008c; Redmond et al, 2008; Boenterd et al, 2010; Calvert et al, 2012; Boentert et al, 2014), resulting in the current clinical presentation.…”
Section: Resultsmentioning
confidence: 99%